Characterization of aEEG During Sleep and Wakefulness in Healthy Children - Löffelhardt, Verena T.; Della Marina, Adela; Greve, Sandra; Müller, Hanna; Felderhoff-Müser, Ursula; Dohna-Schwake, Christian; Bruns, Nora (Frontiers in Pediatrics, 2022)
Introduction: Interpretation of amplitude-integrated EEG (aEEG) is hindered by lacking knowledge on physiological background patterns in children. The aim of this study was to find out whether aEEG differs between wakefulness and sleep in children. Methods: Forty continuous full-channel EEGs (cEEG) recorded during the afternoon and overnight in patients < 18 years of age without pathologies or only solitary interictal epileptiform discharges were converted into aEEGs. Upper and lower amplitudes of the C3 – C4, P3 – P4, C3 – P3, C4 – P4, and Fp1 – Fp2 channels were measured during wakefulness and sleep by two investigators and bandwidths (BW) calculated. Sleep states were assessed according to the American Academy of Sleep Medicine. Median and interquartile ranges (IQR) were calculated to compare the values of amplitudes and bandwidth between wakefulness and sleep. Results: Median age was 9.9 years (IQR 6.1 – 14.7). All patients displayed continuous background patterns. Amplitudes and BW differed between wakefulness and sleep with median amplitude values of the C3-C4 channel 35 µV (IQR: 27 – 49) for the upper and 13 µV (10 – 19) for the lower amplitude. The BW was 29 µV (21 – 34). During sleep, episodes with high amplitudes (upper: 99 µV (71 – 125), lower: 35 µV (25 – 44), BW 63 µV (44 – 81)) corresponded to sleep states N2 – N3. High amplitude-sections were interrupted by low amplitude-sections, which became the longer towards the morning (upper amplitude: 39 µV (30 – 51), lower: 16 µV (11 – 20), BW 23 µV (19 – 31)). Low amplitude-sections were associated with sleep states REM, N1, and N2. With increasing age, amplitudes and bandwidths declined. Conclusion: aEEGs in non-critically ill children displayed a wide range of amplitudes and bandwidths. Amplitudes were low during wakefulness and light sleep and high during deep sleep. Interpretation of pediatric aEEG background patterns must take into account the state of wakefulness in in clinical practice and research.